PENGARUH PEMBELAJARAN PENEMUAN TERBIMBING TERHADAP KEAKTIFAN SISWA DAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP - Andika Hervian Sanjaya Putra (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2015)
This research aims to determine (1) the students’ activation in studying mathematics who are taught by the guided discovery learning is better than the students’ activation in studying mathematics who are taught by the conventional learning, (2) the students’ mathematics studying achievement who are taught by the guided discovery learning is better than the students’ mathematics studying achievement who are taught by the conventional learning. This research is a quantitative Quasi Experimental Designs. It was implemented to the second semester students of the academic year 2014/2015 of Junior High School 6 Madiun with the class VIII as population. While, the sample of this research was the students of the class VIII C as control class using conventional learning, then class VIII D as an experimental class using guided discovery learning. The techniques of data collection used were questionnaire and test. The techniques of data withdrawal used were cluster random sampling. The instrument used students’ activation questionnaire and studying achievement test. The second research instrument before tested in advance validated. Result of research and analysis of data obtained: (1) the students’ activation in studying mathematics who are taught by the guided discovery learning is not better than the students’ activation in studying mathematics who are taught by the conventional learning, (2) the students’ mathematics studying achievement who are taught by the guided discovery learning is not better than the students’ mathematics studying achievement who are taught by the conventional learning. Keywords: Students’ Activation, Mathematics Studying Achievement, Guided Discovery Learning.